2019
DOI: 10.2147/idr.s188538
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance profiles and trends in drug-resistant tuberculosis at a major hospital in Guizhou Province of China

Abstract: Objectives: Tuberculosis (TB) is the leading cause of death from infectious diseases in the world, with an estimated 1.6 million deaths from TB in 2017. The objectives of this study were to determine drug resistance profiles of Mycobacterium tuberculosis clinical isolates and to analyze the trends in drug-resistant and multidrug-resistant tuberculosis (MDR-TB) from 2008 to 2015 at a major hospital in Guizhou, a high-TB burden and resource-limited province of China. Patients and methods: A total of 462 clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
5
13
1
Order By: Relevance
“…During the current study, M. tuberculosis clinical isolates were collected from 318 TB patients and the proportion of male to female patients was 61.6% to 38.4%, which was consistent with our previous study for male (62.8%) and female (37.2%) patients 15. However, the proportion of previously treated cases in this study (41.2%) was higher than that in our previous study (31%),15 probably because only in-patients were enrolled in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…During the current study, M. tuberculosis clinical isolates were collected from 318 TB patients and the proportion of male to female patients was 61.6% to 38.4%, which was consistent with our previous study for male (62.8%) and female (37.2%) patients 15. However, the proportion of previously treated cases in this study (41.2%) was higher than that in our previous study (31%),15 probably because only in-patients were enrolled in this study.…”
Section: Discussionsupporting
confidence: 91%
“…During the current study, M. tuberculosis clinical isolates were collected from 318 TB patients and the proportion of male to female patients was 61.6% to 38.4%, which was consistent with our previous study for male (62.8%) and female (37.2%) patients 15. However, the proportion of previously treated cases in this study (41.2%) was higher than that in our previous study (31%),15 probably because only in-patients were enrolled in this study. For the same reason, rates of MDR-TB in new (18.7%, 35/187) and previously treated TB cases (69.7%, 89/131) were higher than those in our previous studies15 and combined data from 53 Member States in the WHO European Region (15.7% of new and 45.3% of previously treated cases of TB were MDR-TB) 16.…”
Section: Discussionsupporting
confidence: 91%
“…The proportions of MDR- and XDR-TB in this study were 9.5% and 1.1%, similar to the data from Shandong,20 but lower than data from Beijing,19 Guizhou,18 Jiangxi,17 Hunan,9 Shanghai21 and Xinjiang 16. These findings confirmed that there is a wide variation in drug resistance among regions in China.…”
Section: Discussionsupporting
confidence: 83%
“…Among 10 pre-XDR-TB isolates, 90% were previously treated with first line drug for active TB disease although not statistically significant (p = 0.07). This variation in drug resistance patterns of MDR-TB isolates is due to mutational heterogeneity in mycobacterial genes associated with anti-TB drug resistance [36], and also could be due to transmission from person-to-person and de novo evolution of resistance. WHO suggested that treatment decisions should be guided based on the patient's clinical history and recent surveillance data in settings with lack of SLDs DST [37].…”
Section: Discussionmentioning
confidence: 99%